Exploring the potential of imines as antiprotozoan agents with focus on t. Brucei and p. Falciparum - Oluwafemi, Kola Augustus (Rhodes University, Faculty of Science, Department of Chemistry, 2018)
This work focuses on the design, synthesis and evaluation of imine-containing heterocyclic and acyclic compounds with special focus on their bioactivity against parasitic protozoans (P. falciparum and T. brucei) - given the context of drug resistance in the treatment of malaria and Human African sleeping sickness and the fact that several bioactive organic compounds have been reported to possess the imino group. Starting from 2-aminopyridine, novel #-alkylated-5-bromo-7-azabenzimidazoles and substituted 5-bromo-1-(carbamoylmethy)-7-azabenzimidazole derivatives were prepared, and their bioactivity against parasitic protozoans was assessed. NMR spectra of the substituted 5- bromo-1-(carbamoylmethy)-7-azabenzimidazole derivatives exhibited rotational isomerism, and a dynamic NMR study was used in the estimation of the rate constants and the free- energies of activation for rotation. The free-energy differences between the two rotamers were determined and the more stable conformations were predicted. Novel 2-phenyl-7-azabenzimidazoles were also synthesised from 2-aminopyridine. A convenient method for the regioselective formylation of 2,3-diaminopyridines into 2-amino- 7-(benzylimino)pyridine analogues of 2-phenyl-7-azabenzimidazole was developed, and some of the resulting imino derivatives were hydrogenated to verify the importance of the imino moiety for bioactivity. The 2-phenyl-7-azabenzimidazoles and the 2-amino-7- (benzylimino)pyridine analogues were screened for their anti-protozoal activity and their cytotoxicity level was determined against the HeLa cell line. In order to validate the importance of the pyridine moiety, novel #-(phenyl)-2- hydroxybenzylimines, #-(benzyl)-2-hydroxybenzylimines and (Â±)-trans-1,2-bis[2- hydroxybenzylimino]cyclohexanes were also synthesized and screened for activity against the parasitic protozoans and for cytotoxicity against the HeLa cell line. The biological assay results indicated that these compounds are not significantly cytotoxic and a good number of them show potential as lead compounds for the development of new malaria and trypanosomiasis drugs.
Keywords: Protozoa; Parasites; Imines; Nuclear magnetic resonance; HeLa cells; Plasmodium falciparum; Trypanosoma brucei; Isomerism